Chitosan-Polyethylene Glycol Blend Films as Local Ophthalmic Drug Delivery Units: in vitro Studies and Factors Influencing Drug Release - DAMODHARAN, N.; KRISHNAMOORTHY, B.; SENTHIL KUMAR, B.; SOUNDRAPANDIAN, C. (Asian Journal of Chemistry, 2010)
Chitosan and polyethylene glycol (PEG) blend films with gatifloxacin as model drug were fabricated for local ophthalmic delivery. Mechanical characterization and influence of various parameters on drug release were also studied. The results of drug release studies showed that the amount of gatifloxacin released increased with an increase in the proportion of polyethylene glycol and decreased as the amount of drug loaded in the film increased. Gatifloxacin release was also sensitive to ionic strength and declined as the film thickness, sodium alginate coat thickness, cross-linking time increased.